Feasibility analysis of the conversion of brushed to brushless direct current motor - Pudji Irasari; Puji Widiyanto; Anwar Muqorobin; Muhammad Fathul Hikmawan (Institute of Advanced Engineering and Science, 2023)
This paper analyzes the feasibility of converting brushed direct current (BDC) to brushless direct current (BLDC) motor by substituting the wound rotor with a permanent magnet. The aim is to overcome the low quality of rewinding of wound rotors. The conversion was performed by redesigning the motor, referring to the old stator dimensions and motor specifications. Some suitable speed control systems were also examined. Technical analysis was executed by simulating motor characteristics, covering torque-speed curve, cogging, and ripple torques. Afterward, an economic analysis was done to determine the cost of making one rotor unit and the speed control and then compare it with the price of a new BDC motor with equivalent power. The results show that the motor produces 3.6 kW, 18.86 V, 176.71 A, and 28.53 Nm at 2,460 rpm with 2 phases configuration. The maximum cogging torque is 2.9 Nm. The cost of making one rotor unit plus speed control is higher than that of a new BDC motor. These results show that it is technically feasible to convert BDC into a BLDC motor but not economically or vice versa.